Search for W H associated production in 5.3 fb(-1) of p(p)over-bar collisions at the Fermilab Tevatron - Abazov, V.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; Aoki, M.; et al. (Elsevier, 2011)
We present a search for associated production of Higgs and W bosons in pp̄ collisions at a center of mass energy of s=1.96 TeV in 5.3 fb-1 of integrated luminosity recorded by the D0 experiment. Multivariate analysis techniques are applied to events containing one lepton, an imbalance in transverse energy, and one or two b-tagged jets to discriminate a potential WH signal from Standard Model backgrounds. We observe good agreement between data and expected backgrounds, and set an upper limit of 4.5 (at 95% confidence level and for mH=115 GeV) on the ratio of the WH cross section multiplied by the branching fraction of H→bb̄ to its Standard Model prediction, which is consistent with an expected limit of 4.8. © 2011 Elsevier B.V.
Keywords: Electroweak symmetry breaking.; Higgs boson; Standard Model; Tevatron